Culex pipiens affected by joint infection of a mosquito iridescent virus and Strelkovimermis spiculatus - Muttis, Evangelina (2013)
Dual infections with a mosquito iridescent virus (MIV) and the mermithid nematode, Strelkovimermis spiculatus were recorded in natural Culex pipiens populations around La Plata city, Argentina. S. spiculatus was detected in 82% of samples that were positive for MIV infection. Dissected larvae of Cx. pipiens with patent MIV infection presented 42% infection with S. spiculatus. Larvae of Cx. pipiens exposed to MIV and S. spiculatus under laboratory conditions produced a high joint infection rate (82.5%) while no infection was recorded on larvae exposed to virus suspension only. Field and laboratory results suggest a strong association between S. spiculatus and MIV in natural populations of Cx. pipiens, in which S. spiculatus could be a mode of entry for the virus into the mosquito hemocele.